Performing new lives : prison theatre - Shailor, Jonathan (Jessica Kingsley Publishers, 2010)
Performing New Lives draws together some of the most original and innovative programs in contemporary prison theatre. Leading prison theatre directors and practitioners discuss the prison theatre experience first-hand, and offer valuable insights into its role, function, and implementation. A wide range of prison theatre initiatives are discussed, from long-running, high-profile programs such as Curt Tofteland's Shakespeare Behind Bars" in LaGrange, Kentucky, to fledgling efforts like Jodi Jinks' "ArtsAloud" project in Austin, Texas. The book offers unique insights into the man.